La relación del proceso de la capacitación y el desempeño laboral de empresas privadas y públicas - Talledo Peñaloza, Cristobal Manuel (2022)
The professional development of employees is becoming a key strategy for organizations to be competitive in today's market. Therefore, the training process plays an important role in the growth of organizations. The objective of this paper was to analyze the relationship between the training process in job performance in private and public companies, with the review of ten scientific studies that meet the inclusion and exclusion criteria proposed. As results, it was found, within the articles, relationships on the different phases of the training process (diagnosis, design, application, and evaluation) with job performance. Each stage of the training process maintains a relationship with the increase in individual work performance, within the development of competencies, as well as institutional, in the achievement of company objectives. Finally, the main limitation of the project is the difficulty of standardizing the evaluation process of the variables studied, which leads to a lack of validity reporting in the analyzed publications.